2015
DOI: 10.1177/070674371506000105
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Employment Status in Primary and Tertiary Care Settings

Abstract: Unemployment and disability rates in MDD are high. The presence of anhedonia and medical comorbidity significantly influenced work status, emphasizing the need for treatment strategies to alleviate the additional symptom burden in this subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 41 publications
2
53
2
1
Order By: Relevance
“…41 In Canada, workers with MDD, compared to those without depression, were twice as likely to leave work during a 10-year follow-up. 42 Increased severity of illness, 43 concurrent medical conditions, 44 and comorbid anxiety disorders 45 result in a higher degree of work disability and greater absenteeism in people with MDD. In addition to overall severity, individual symptoms of MDD can differentially affect workplace performance.…”
Section: What Is the Occupational Impact Of Mdd?mentioning
confidence: 99%
“…41 In Canada, workers with MDD, compared to those without depression, were twice as likely to leave work during a 10-year follow-up. 42 Increased severity of illness, 43 concurrent medical conditions, 44 and comorbid anxiety disorders 45 result in a higher degree of work disability and greater absenteeism in people with MDD. In addition to overall severity, individual symptoms of MDD can differentially affect workplace performance.…”
Section: What Is the Occupational Impact Of Mdd?mentioning
confidence: 99%
“…Major depressive disorder (MDD), or unipolar depression (henceforth referred to as 'depression'), has a significant negative impact on life functioning and on work-related outcomes such as employment status [1][2][3][4][5] and work productivity, including absenteeism and presenteeism [2,6]. In fact, MDD has one of the highest levels of negative impact on work outcomes, higher than rheumatoid arthritis [7,8], ischemic heart disease [8], and other mood disorders including anxiety [9].…”
Section: Introductionmentioning
confidence: 98%
“…When people are socially excluded or have a greater sensitivity to rejection, four fundamental needs are proposed to be affected: belonging, self-esteem, control and meaningful existence which are required for human survival and effective social functioning (Williams, Cheung, & Choi, 2000). The impairment of social functioning is proposed to be reliable indicator of depression (Cheng & Furnham, 2003;Hirschfeld et al, 2000) and these dysfunctions in social interactions were reported to persist even after three years of recovery from depressive symptoms (Rhebergen et al, 2010) and correlated with unemployment, disability and decreased work performance (Rizvi et al, 2015). Further, depressed individuals possess specific traits that increase the likelihood they will experience interpersonal stress and have subsequent depressive episodes (Hammen, 2005).…”
Section: Introductionmentioning
confidence: 99%